Evaluation of Basalt Fibers on Wind Turbine Blades through Finite Element Analysis. (18th April 2019) - García, V.; Vargas, L.; Acuña, A.; Sosa, J. B.; Durazo, E.; Ballesteros, R.; Ocampo, J.
Abstract : Here we use finite element analysis to determine the suitability of basalt fiber as a substitute for E-glass in structural applications, which would improve the cost effectiveness of small wind turbine blades. Five NACA (National Advisory Committee for Aeronautics) profiles were evaluated to select the optimum shape for the wind operation conditions. To obtain the wind load pressure distribution over the blade, a computational aerodynamic analysis by CFD (computational fluid dynamics) was performed based on the blade's design and operating conditions. Material properties and mechanical tests were carried out to obtain the fiber volume fraction, density, Young's modulus, shear modulus, and Poisson relation of polymeric matrix composites made using basalt and fiberglass. The obtained wind loads and material properties were used on a FEM (finite element model) analysis to evaluate the structural behavior of the blade under normal and critical operating conditions. Both fibers meet the structural requirements under normal operating conditions. We detected a reduction of 4% in the blade stress when basalt fibers are used instead of glass fibers, and a reduction of 68% in the total deformation for a critical load case of 40 m/s was obtained when using basalt fibers, which met the structural requirements and maximum power generation required for this wind turbine design.